Bishop Broughton and his Colonial Visitation in 1845 - Willson, Robert (Journal of Anglican studies, 2024)
This article examines an account by William Grant Broughton, describing a journey made in 1845 to the south of his Diocese of Australia. It was published by English supporters, describing the impossibly large area of his responsibility and pleading for a subdivision of his diocese. Broughton wanted to overcome ignorance of Australia, to thank his supporters for money and manpower, and to demonstrate that his work as a bishop was not just a state appointed official, but as a spiritual Father-in-God in apostolic succession from Christ. Broughton was inspired by the Oxford Movement. Broughton met influential colonists and inspired support in his vision of church buildings where the Gospel might be preached and the sacraments of the Church of England celebrated with a dignity to inspire and attract the flock. Broughton knew the 1836 decision of the Government to give state aid to all major Christian denominations undermined the claim of the Church of England to have inherited established legal status the church enjoyed in England. Broughton’s heroic efforts form an inspiring Anglican heritage. The article concludes that by the time of his death in 1853 his church was but one denomination in a spiritually plural, and secular, society.